Endometrial polyps with bizarre stromal cells: a Benign or a low-grade lesion? - Musen Wang; Fei Gao; Hongkai Zhang; Wenxin Zheng (BMC Women's Health)
Abstract Background Polyps containing bizarre stromal cells are occasionally observed in the lower gynecologic tract, including the vagina, cervix, and endometrium, predominantly in perimenopausal or postmenopausal patients. These cases have traditionally been considered benign without subsequent recurrence or malignancy. Case presentation We describe a rare instance of a rapid enlarging endometrial polyp characterized by atypical stromal cells in a 76-year-old postmenopausal woman, who presented with vaginal bleeding. Histologically, the polyp was noted for its abundance of atypical stromal cells interspersed among thick-walled vascular channels. Higher magnification revealed eosinophilic cytoplasm in the stromal cells, which exhibited both mono- and multinucleation, hyperchromasia with coarse chromatin, and an absence of conspicuous nucleoli and mitotic figures. A consensus among two of three consulting expert gynecological pathologists supported a benign endometrial polyp diagnosis; however, one pathologist raised the possibility of adenosarcoma, highlighting the diagnostic dilemma these unique lesions present. Despite a hysterectomy recommendation, the patient chose monitoring over immediate surgery. Persistent vaginal bleeding led to her return six months later, whereupon a 7-cm polypoid lesion in the endometrial cavity was found and removed via hysterectomy. The histopathology mirrored the initial findings, showing no myometrial invasion, prompting a re-evaluation of the presumed benign nature of the polyp given its rapid growth. Remarkably, RNA sequencing analysis of the polyp detected a JAK2::NFIB gene fusion, a novel finding for endometrial polyps with atypical stromal cells, the clinical implications of which remain to be elucidated. Conclusion The rapid recurrence of the polyp within six months raises new questions about the true biological nature of these entities and the relevance of gene fusions like JAK2::NFIB in their pathogenesis, meriting further investigation.